(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
New results of complex studies of four high-altitude lakes of Armenia (Kari, Umroy, Akna and Sev) are presented. For the first time, changes in the natural environment in the Holocene were reconstructed for these lakes according to complex palynological analysis, their digital models were created as well. The modern morphometric characteristics of lake basins were clarified and the features of underwater relief and conditions for the accumulation of bottom sediments in lakes were identified. For the first time, bathymetry of lake basins and sampling of bottom sediment cores from different depths were carried out. Radiocarbon dating of lake sediments and an idea of their structure were obtained. According to the characteristic relief of the terminal moraines of the cirque glaciers, it was possible to distinguish four stages of retreat of the glacier of the last glaciation for Aragats area after its maximum advance: the lowest position is 3100–3000 m, the second stage is 3200–3100 m, the third stage is 3300–3200 m, the fourth stage is 3400–3300 m. The data testifying to the presence of natural rhythms in the development of the highland belt of Armenia, measured for thousands of years have been revealed. The period of warming and humidification of the climate corresponding to the time interval of 3000–2000 Cal years ago is highlighted, i.e. the period of widespread forests and maximum dynamics of the upper forest boundary. Precipitation with a maximum content of organic matter (30–50%) accumulated in the lakes of the mountainous belt of Armenia. It is proven that the thickness of the bottom sediments of Lake Kari was formed in 4000 years, and in Lake Umroy – in 8000 years. Warm periods with the appearance of forest vegetation in the modern high-altitude zone occurred even when the anthropogenic factor could not contribute to climate warming on the territory of Armenia – at that time there was no modern industry with greenhouse gas emissions into the atmosphere. It can be argued that the current warming of the climate on Earth is not the result of the emission of greenhouse gases by industrial facilities, but only a natural rhythm.